1999
DOI: 10.2331/fishsci.65.138
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cross-linking of Fish Myofibrillar Proteins by Endogenous and Microbial Transglutaminases

Abstract: The cross-linking reaction was performed in the medium containing fish myofibrillar proteins, 0.5 M (or 0.1 M) NaCl, and 5 mm CaCl2 at pH 7.5 and 25•Ž with transglutaminases from carp muscle and the culture filtrate of a strain of Streptoverticillium mobaraense. Carp enzyme (CTGase) preferentially polymerized myosin heavy chains among individual myofibrillar components. Microbial enzyme (MTGase) also rapidly cross-linked myosin heavy chains at different sites from those with CTGase. Con nectin (titin) was poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…Generally, shrimp meat has the poor gel forming ability, which is possibly associated with the low setting phenomenon or the inappropriate protein structure for cross-linking or gelation. Though MTGase has been successfully used for improving the gel property of various proteins including surimi (Nakahara, Nozawa, & Seki, 1999;Nonaka et al, 1989;Tanaka, Nonaka, & Motoki, 1990), no information regarding the use of MTGase in shrimp meat, especially from white shrimp, has been reported. The objective of this study was to investigate the influence of MTGase in combination with setting on the gel properties of white shrimp meat.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, shrimp meat has the poor gel forming ability, which is possibly associated with the low setting phenomenon or the inappropriate protein structure for cross-linking or gelation. Though MTGase has been successfully used for improving the gel property of various proteins including surimi (Nakahara, Nozawa, & Seki, 1999;Nonaka et al, 1989;Tanaka, Nonaka, & Motoki, 1990), no information regarding the use of MTGase in shrimp meat, especially from white shrimp, has been reported. The objective of this study was to investigate the influence of MTGase in combination with setting on the gel properties of white shrimp meat.…”
Section: Introductionmentioning
confidence: 99%
“…No marked changes in actin were obtained in the presence and absence of MTGase. Nakahara and others (1999) reported that MTGase and carp TGase could not cross‐link actin molecules. The decrease in MHC band intensity was concomitant with the increased breaking force and deformation (Figure 1).…”
mentioning
confidence: 99%
“…Similar observations were reported by Nakahara et al . (), who revealed that MTGase preferentially cross‐linked connectin, followed by MHC, troponin T and actin, respectively. In contrast, no changes were found in the content of actin obtained from beef (Dondero et al .…”
Section: Resultsmentioning
confidence: 99%